Incidence of Inadvertent Intravascular Injection during CT Fluoroscopy–Guided Epidural Steroid Injections - Kranz, P.G.; Amrhein, T.J.; Gray, L. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Inadvertent intravascular injection during epidural steroid injection can result in complications and has been investigated previously with conventional fluoroscopy, but not CT fluoroscopy. The purpose of this study was to determine the incidence of intravascular injections recognized during CT fluoroscopy–guided epidural steroid injection. MATERIALS AND METHODS: We retrospectively reviewed 575 consecutive CT fluoroscopy–guided epidural steroid injections. Procedures were assessed to determine the incidence of intravascular injection. Cases positive for intravascular injection were classified on the basis of anatomic location, distance from the needle tip, washout pattern, and presence of combined epidural and vascular injection. Cases were also graded as either venous or arterial by using a 5-point scale. RESULTS: Intravascular injection was observed in 26% of cervical transforaminal epidural steroid injections (7/27), 9% of cervical interlaminar epidural steroid injections (4/47), 8% of lumbar transforaminal epidural steroid injections (22/275), and 2% of lumbar interlaminar epidural steroid injections (4/222). Vessels were most commonly identified close to the needle, but in 30% of cases, they were visualized in the anterior paraspinal soft tissues remote from the needle. Washout was most commonly delayed (86%), though rapid washout occurred in 14% of cases. Simultaneous epidural and vascular injections occurred in 32% of cases. Most visualized vessels were venous, but 2 cases were classified as probably arterial. CONCLUSIONS: Intravascular injections can be detected with CT fluoroscopy. The incidence in our study was similar to that in previous reports using conventional fluoroscopy. Technical factors such as the “double-tap” on CT fluoroscopy following contrast injection, assessment for discordance between injected and visualized contrast volume, and maintenance of an appropriate FOV facilitate the detection of such events. CTFCT fluoroscopyESIepidural steroid injectionILESIinterlaminar epidural steroid injectionTFESItransforaminal epidural steroid injection